"Shehar Khali Kocha Khali": A Postmodern Perspective of the Novel Written in the Covid-19 Scenario - Noon, Yousaf; Asghar, Ghulam; Abbas, Tahir (sourcecoder, 2022)
Corona has changed the scenario of world and life. World history is full of epidemics, when these epidemics cause destruction, at the same time they are the great stimulus for literary creations. In Urdu literature, Tatar's novel "Shehar Khali Kocha Khali" is also outcome of the Covid-19 scenario. The novelist has utilized his experience of the Corona encounter in his literary work. In this research article, impacts of Corona on human nature, ideologies, values and environment has been examined through the novel. Corona not only has refuted the manmade mega narratives but also has affected the environment a lot. Effects of Corona on environment has been assessed under environmental criticisms. Postmodernism on one hand refutes the mega narratives and universal truths established by modernism and premodernism, on other hand, it, with the help of environmental philosophy, leads how we can get rid of effects of modernism on environment and how the environment can be rehabilitated.